Scoping study on participatory rangeland management (PRM) in Wajir - International Livestock Research Institute (International Livestock Research Institute, 2022)
This report is a contribution to ILRI's RECONCILE project Livestock, Climate and System Resilience (LCSR), a research program that aims to improve participatory rangeland management (PRM) uptake by establishing a stronger technical base. The three-year project builds on the gains and lessons learned in the implementation of PRM in Baringo implemented under similar collaborative arrangements and promoted PRM both as a concept for rangelands management and restoration and as a process that promotes sustainable land use, policy and governance of rangelands and pastoral livelihoods systems. PRM was conceived as a regional project also piloted in Tanzania to complement the legal land use tenure security of the Joint Village Land Use Planning. A similar intervention has been successfully implemented through a pilot phase in Ethiopia where it was confirmed as an important concept in addressing rangeland degradation and other rangeland-based challenges where, over the years, rangelands have experienced pressure from a number of threats.